Impact of Video Recorded Lectures on Learning at Radboud University, Netherlands - Bagarukayo, Emily; Mbarika, Victor; Weide, Theo van der (GlobDev, 2011)
Due to the continuous emergence of new technology, more and more students want to use technology for learning. Digital technology has become part of students‟ life today, hence the term Digital Natives in reference to today‟s students. A pilot survey was carried out at Radboud University, Netherlands to determine the impact of video recorded lectures on the students learning process. We present the findings from the survey indicating that students benefitted from the videos. The results we present reveal that the videos are often used to prepare for exams, future classes, catch up with missed classes, among others. The students appreciate the immediate availability of the information on video, the fact that they are able to make the most of micro moments; and they believe they perform better with the recorded videos, among other benefits. The researchers also give some recommendations for introducing the video recorded lectures in Least Developing Countries (LDCs).
Keywords: Videos; Video recorded lectures; Learning; Learning Styles